The Analysis of Interpersonal Meaning (MOOD), Ideational Meaning (TRANSITIVITY) and Textual Meaning (THEME) of News Item Text Entitled “Nikita Mirzani: I`m Not a Prostitute” - Indra Yoga Prawiro (Universitas Wiralodra, 2017)
Today, media has become primary needs as food and clothing. It has played significant role in strengthening the society that is as a